Relationships of Tobacco Use and Kava Consumption to Sex-Associated Variation in Body Composition and Obesity Risk in Melanesian Adults From Vanuatu. (September 2022) - Olszowy, Kathryn M.; Roome, Amanda B.; Standard, Elisabeth; Tarivonda, Len; Taleo, George; Dancause, Kelsey N.
Obesity prevalence has increased in low- and middle-income countries (LMICs) over the past several decades, with generally greater occurrence among adult females compared with males. Gendered variation in health behaviors, such as substance use, may play a role in how differences in obesity, body size, and composition manifest in association with sex. This study examines sex-moderated relationships of tobacco smoking and kava consumption with body composition and obesity among 301 Ni-Vanuatu (local self-identification meaning "of Vanuatu") adults. Data collected included self-reported frequency of substance use as well as anthropometric measurements to assess body mass, composition, and obesity. Tobacco and kava use were associated with reduced measurements of body mass and adiposity in males, and kava use was associated with some elevated measurements of body mass and hip circumference in females. Kava use was also negatively associated with obesity based on waist-to-height ratio among males. These results have implications for evaluation and future research on substance control programs in this population.